Emancipatory movements in composition : the rhetoric of possibility - Greenbaum, Andrea (State University of New York Press, 2002)
"Emancipatory Movements in Composition provides an overview of the four major disciplines that have, for the last ten years, influenced and guided the direction of composition studies. Drawing on contemporary social and rhetorical theory, this is the first cultural studies text deeply informed by classical rhetoric, feminism, and postcolonial studies. It merges theory and pedagogy, providing a rubric for understanding critical pedagogy, neosophistic rhetoric, service-learning, and enthnographic research."--Jacket.